Hands-on Netscape - Sachs, David (Prentice Hall International, 1996)
Master the most popular and fastest Internet navigation software with Hands-On Netscape. With the video tutorial on the CD, Netscape users can learn by seeing as well as by reading. Includes the "downloader's companion" for Netscape including all the helper applications needed to run full multimedia. The CD also includes software tools for surfing the multimedia Internet.